Augmented reality mobile application and its influence in Quechua language learning - Camacho Montellanos, José Luis (2020)
Augmented reality technology is being a huge support in education standing out the user's attention to interact with virtual world in real space. In this article, the level of influence that would have the use of a mobile application with augmented reality will be evaluated in primary students for Quechua language learning. Likewise, the quasi-experimental design is used and the sample consists of sixty students divided into two classrooms of thirty students respectively. The experimental group improves his grades in a 19.7% unlike the control group and also a reduction of time for understanding the information is seen. In conclusion, the augmented reality mobile application influences significantly in Quechua language learning for fourth-year pupils of primary school.